Effectiveness of a yoga program in decreasing anxiety and depression symptoms among women in Gaza strip - Alsahhar, Khitam I. M.; Al-Sirafi, Marwa Yousef (Journal of Advanced Education and Sciences, 2026)
This study investigates the effectiveness of a yoga-based therapeutic program in reducing symptoms of anxiety and depression among women in the Gaza Strip, a context characterized by chronic psychosocial stressors and limited access to mental health services. The study employed a quasi-experimental design with a pre–post control group approach. A total of 70 participants were randomly assigned into experimental (n = 35) and control (n = 35) groups. Standardized instruments were utilized, including the Generalized Anxiety Disorder Scale (GAD-7) and the Patient Health Questionnaire (PHQ-9). The intervention consisted of a structured 12-session yoga program integrating breathing techniques, physical postures, relaxation, and mindfulness-based practices. Data were analyzed using SPSS (Version 26), applying parametric statistical tests, including paired and independent sample t-tests, as well as ANOVA. The findings revealed statistically significant reductions in anxiety and depression symptoms among the experimental group compared to the control group (p ≤ 0.05), with large effect sizes (η² = 0.81 for anxiety; η² = 0.79 for depression). Furthermore, follow-up results indicated sustained improvements one month after the intervention. No statistically significant differences were found across demographic variables, suggesting the program’s broad applicability. The study concludes that yoga-based interventions represent a cost-effective, scalable, and culturally adaptable approach for improving mental health outcomes among women in high-stress environments. The findings hold important implications for integrating mind–body interventions into community mental health frameworks, particularly in conflict-affected regions.